2004
DOI: 10.1029/2003gb002180
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐D model analysis of the slowdown and interannual variability in the methane growth rate from 1988 to 1997

Abstract: Methane has exhibited significant interannual variability with a slowdown in its growth rate beginning in the 1980s. We use a 3‐D chemical transport model accounting for interannually varying emissions, transport, and sinks to analyze trends in CH4 from 1988 to 1997. Variations in CH4 sources were based on meteorological and country‐level socioeconomic data. An inverse method was used to optimize the strengths of sources and sinks for a base year, 1994. We present a best‐guess budget along with sensitivity tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
224
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(239 citation statements)
references
References 99 publications
10
224
0
Order By: Relevance
“…Palmer et al, 2003), methane (e.g. Wang et al, 2004), and carbon dioxide (e.g. Fraser et al, 2014), and have also recently been used in mercury studies.…”
Section: Inverse Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Palmer et al, 2003), methane (e.g. Wang et al, 2004), and carbon dioxide (e.g. Fraser et al, 2014), and have also recently been used in mercury studies.…”
Section: Inverse Modelmentioning
confidence: 99%
“…30 We construct the observation error covariance matrix, , as a diagonal matrix (dimension 268×268) with the elements the square of the measurement error. We take the measurement error to be the sum in quadrature of the instrumental error and the mean station model-mismatch error (Wang et al, 2004). The model-mismatch error attempts to account for model transport error, and sub-grid scale variations in Hg concentrations.…”
Section: Inverse Modelmentioning
confidence: 99%
“…although with significant uncertainties still remaining about the exact magnitude of each identified source and sink (Ehhalt et al 2001;Wang et al 2004;Frankenberg et al 2005;do Carmo et al 2006). Keppler et al (2006) recently reported that CH 4 was emitted from dead and living plant material under aerobic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Upper and lower panels show data on 1000-year and 50-year time axes, respectively. Fletcher et al 2004a;Mikaloff Fletcher et al 2004bWang et al 2004Wang et al et al 2004 (W2004); Prinn 2005 (CP2005). A 4-level greyscale is used to distinguish studies, cycling 3 times through the 12 available studies.…”
Section: Acknowledgmentsmentioning
confidence: 99%